Identifikasi Sampah Laut (Marine Debris) di Pantai Petitenget, Bali - Sembiring, Cindy Claudya Br; Ulinuha, Devi; Saraswati, Ni Luh Gede Rai Ayu (Current Trends in Aquatic Science, 2023)
Marine debris has caused various problems to the environment, including transporting contaminants and invasive species. Moreover, it also, has an impact on socio-economic of coastal community and on the sustainability of marine biota and its cosystem. The aim of this research is to identify the characteristics and quantity of waste generation (weight, composition, and density) in Petitenget Beach. The study was conducted from October to December 2022. The data collection method was carried out by purposive sampling based on Ministry of Environment and Forestry 2020 Beach Waste Monitoring Guidelines. The results showed that the majority types of macro-inorganic waste found on Petitenget Beach were plastics, which was categorized as foamed plastic, glass, rubber, cloth, metal, and other materials. For this type of inorganic waste, meso-inorganic waste consists of plastic and foamed plastic. Plastic has the highest mass, waste composition and density of inorganic waste found on Petitenget Beach, 0.2017 gr/m², 93,5% and 0.0733 items/m², respectively. Overall, this study shows that plastic waste has polluted both beaches with high mass, amount, type composition, and density. The oceanographic conditions during the study, namely the highest current speed occurred in November, namely 0.7 m/s, the wave height of the sea water at Petitenget Beach during the study period ranged from 1.1 m-2.5 m. The highest water movement at high tide reaches 2.17 m and at low tide reaches 0.25 m.